Direct Observations of Energetic Electron Scattering and Precipitation Due To Whistler‐Mode Waves in the Dayside High‐Density Regions. Issue 3 (2nd March 2023) - Sugo, Shin; Kasahara, Satoshi; Miyoshi, Yoshizumi; Katoh, Yuto; Keika, Kunihiro; Yokota, Shoichiro; Hori, Tomoaki; Kasahara, Yoshiya; Matsuda, Shoya; Matsuoka, Ayako; Shinohara, Iku; Tsuchiya, Fuminori; et al.
Abstract: Plasmaspheric hiss waves play an important role in electron precipitation, leading to the formation of slot region in the Earth's radiation belt. Previous studies indicate that the electron density and the background magnetic field strength are responsible for the intensity of whistler‐mode waves and resultant electron precipitation. Nevertheless, no direct evidence of the strong pitch angle scattering of energetic electrons by hiss waves inside the plasmasphere has been obtained due to the small loss cone near the magnetic equator, where the scattering occurs. Furthermore, the density and magnetic field structures have not been investigated simultaneously and on the same magnetic field lines as the hiss wave enhancement and electron precipitation. With high angular resolution data of ∼10–100 keV electron flux obtained by the Medium‐Energy Particle experiments‐electron analyzer onboard the Exploration of energization and Radiation in Geospace satellite, we identified two events of the strong electron precipitation. A detailed examination revealed that the precipitation occurs in association with the amplitude enhancement of hiss waves. Moreover, strong scattering occurs simultaneously with electron density enhancements, while the magnetic field strength hardly correlates with the wave intensity. Our direct observations indicate that the electron density and its spatial structure (gradient) are crucial to electron precipitation. The observations also indicate that strong scattering leading to substantial loss cone filling occurs up to the magnetic latitude of ∼15° for the events. Key Points: In situ observations directly show that the strong scattering of energetic electrons occurs during plasmaspheric hiss waves enhancement The hiss wave enhancements and electron precipitation are correlated with electron density increase but not with magnetic field intensity Density enhancement may be important for the whistler‐mode wave enhancement and resultant electron precipitation